Supervisi Klinik sebagai Upaya Meningkatkan Kemampuan Guru dalam Mengelola Pembelajaran di SMA Negeri 8 Gowa - Islamuddin Islamuddin (Universitas Pendidikan Mandalika, 2021)
This study aims to improve the ability of teachers to manage learning through clinical supervision. This study uses school action research with the research subjects being teachers at SMA Negeri 8 Gowa. This research instrument uses a questionnaire, observation, and documentation. The data analysis technique used descriptive qualitative and quantitative analysis. The results of this action research indicate that through clinical supervision carried out by the school principal, it has been able to improve the ability of teachers to manage learning, especially in the preparation of learning implementation plans, the ability to manage classes, as well as the implementation of evaluation and assessment. Based on the assessment format data in this study, the number of teachers who scored (70-85) in the high grade category (B) was 6 teachers or (85.71%).